New Basis for Regional and Urban Policies in East-Central Europe - Enyedi, György (Discussion Papers, 1990)
East-Central European countries had adopted the Soviet model of urban and regional development by the late-1940s. The present paper provides a summary of the 40-year history of urban and regional development. First, the author characterizes the principles of regional/urban policies of the Stalinist model, second, he analyzes the applications and changes of these policies during the last 30 years, third, he discusses the impact of political and economic reforms upon the process of regional and urban development. After presenting the regional and urban policies of the Stalinist model, the author discusses the development of new tendencies toward the dissolution of this model. The concluding chapter attempts to characterise the 40 years of urban and regional policy and evaluates the outcome of ‘socialist’ regional development.